1996
DOI: 10.1016/s0006-3495(96)79496-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell motility driven by actin polymerization

Abstract: Certain kinds of cellular movements are apparently driven by actin polymerization. Examples include the lamellipodia of spreading and migrating embryonic cells, and the bacterium Listeria monocytogenes, that propels itself through its host's cytoplasm by constructing behind it a polymerized tail of cross-linked actin filaments. Peskin et al. (1993) formulated a model to explain how a polymerizing filament could rectify the Brownian motion of an object so as to produce unidirectional force (Peskin, C., G. Odell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
842
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 855 publications
(898 citation statements)
references
References 61 publications
32
842
5
Order By: Relevance
“…However, because we discretized angles into six possible orientations, our resolution limits our ability to study the precise details of the preferred orientation. (For example, we cannot explain the dominant angular preference around ±30 • ; but see Mogilner and Oster (1996a); Maly and Borisy (2001). )…”
Section: Internal Architecture Of the Cellmentioning
confidence: 85%
“…However, because we discretized angles into six possible orientations, our resolution limits our ability to study the precise details of the preferred orientation. (For example, we cannot explain the dominant angular preference around ±30 • ; but see Mogilner and Oster (1996a); Maly and Borisy (2001). )…”
Section: Internal Architecture Of the Cellmentioning
confidence: 85%
“…However, cell body translocation was only partially inhibited by blebbistatin, suggesting that either myosin II activity was not completely blocked by this drug or that there are other redundant mechanisms contributing to the cell body translocation. One of the possibilities is that in the absence of myosin activity the force could be produced by the depolymerization-driven entropic network contraction (Mogilner and Oster, 1996). Regardless, fragmentation of the cell suggested that when myosin activity was attenuated, cell body could not follow front protrusion in a robust and effective way.…”
Section: Molecular Biology Of the Cell 3728mentioning
confidence: 99%
“…In such a 'treadmill' the force of actin polymerization at the front is coupled to the disassembly of the actin network at the rear of the lamellipodia, propelling the leading edge forward along the substrate (Machacek and Danuser, 2006;Pollard and Borisy, 2003;Ponti et al, 2004;Watanabe and Mitchison, 2002). Based on actin filament stiffness, it has been calculated that the 'free' length of the actin filaments pushing the leading edge has to be quite short (less than 150 nm) in order to create sufficient force for membrane protrusion (Mogilner and Oster, 1996), suggesting that the filament length in the treadmill must be very tightly regulated to achieve the most efficient forward movement.…”
Section: Basic Principles Of Cell Migration Overall Structure Of the mentioning
confidence: 99%